2016
DOI: 10.1177/0194599816645765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vocal Fold Medialization on Dysphagia in Patients with Unilateral Vocal Fold Immobility

Abstract: Patients with UVFI suffer from dysphagia and report significant improvement in swallowing symptoms following VFM. The symptomatic improvement appears to be durable over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 18 publications
4
72
1
Order By: Relevance
“…24 This hypothesis is also supported by analysis of intrabolus pressures where investigators have observed increasing hypopharyngeal pressures prior to UES relaxation and subsequent subatmospheric pressures just ahead of the bolus head coinciding with UES relaxation. [27][28][29] Although more investigation is needed, surgical interventions aimed at reinstating a pharyngeal chamber during swallowing may benefit patients with dysphagia due to pharyngeal outflow issues (eg, palatal augmentation in treated patients with nasopharyngeal carcinoma). Several investigators have shown pharyngeal swallowing improvement with improvement of glottic competency without specifically commenting on pressure gradients.…”
Section: Discussionmentioning
confidence: 99%
“…24 This hypothesis is also supported by analysis of intrabolus pressures where investigators have observed increasing hypopharyngeal pressures prior to UES relaxation and subsequent subatmospheric pressures just ahead of the bolus head coinciding with UES relaxation. [27][28][29] Although more investigation is needed, surgical interventions aimed at reinstating a pharyngeal chamber during swallowing may benefit patients with dysphagia due to pharyngeal outflow issues (eg, palatal augmentation in treated patients with nasopharyngeal carcinoma). Several investigators have shown pharyngeal swallowing improvement with improvement of glottic competency without specifically commenting on pressure gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroidectomy is the most common procedure which exposes the laryngeal nerves to risk, and our observations emphasise the importance of promptly recognising and treating post‐surgical dysphagia, and actively excluding vocal palsy as its cause. Treatment often takes the form of swallowing therapy with possible dietary modifications to reduce the risk of aspiration pneumonia, and, in selected cases, vocal medialisation surgery which may be undertaken in the immediate post‐operative settings or at a later time following failure of conservative treatment may be helpful …”
Section: Discussionmentioning
confidence: 99%
“…There are a wide range of surgical procedures that place normally functioning laryngeal nerves at risk of injury, which in turn places the patient at risk of post‐operative dysphonia, dysphagia, and less commonly, airway compromise . Thyroidectomy is the commonest of these procedures (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, anecdotally, many patients report improved deglutition and breathing following surgery to improve glottic closure. Emerging data support treatment for glottal insufficiency for dysphagia . However, little evidence exists to support intervention for dyspnea associated with glottic insufficiency.…”
Section: Introductionmentioning
confidence: 99%